2016
DOI: 10.1096/fj.201600539
|View full text |Cite
|
Sign up to set email alerts
|

N‐Homocysteinylation impairs collagen cross‐linking in cystathionine β‐synthase‐deficient mice: a novel mechanism of connective tissue abnormalities

Abstract: Cystathionine β-synthase (CBS) deficiency, a genetic disorder in homocysteine (Hcy) metabolism in humans, elevates plasma Hcy-thiolactone and leads to connective tissue abnormalities that affect the cardiovascular and skeletal systems. However, the underlying mechanism of these abnormalities is not understood. Hcy-thiolactone has the ability to form isopeptide bonds with protein lysine residues, which generates N-homocysteinylated protein. Because lysine residues are involved in collagen cross-linking, N-homoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 55 publications
0
51
0
Order By: Relevance
“…Animal studies show that N ‐Hcy‐protein accumulates within atherosclerotic lesions in aortas of ApoE −/− mice fed with a normal chow diet and that the accumulation increases in the ApoE −/− animals fed with a HHcy diet‐. Other data show that N ‐homocysteinylation impairs collagen cross‐linking in various organs, including the heart, of Cbs −/− mice, thus providing an explanation for connective tissue deficiencies prevalent in HHcy humans . In small, case–control studies, elevated plasma Hcy‐thiolactone and N ‐Hcy‐protein are associated with vascular damage in diabetes and increased CAD risk , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies show that N ‐Hcy‐protein accumulates within atherosclerotic lesions in aortas of ApoE −/− mice fed with a normal chow diet and that the accumulation increases in the ApoE −/− animals fed with a HHcy diet‐. Other data show that N ‐homocysteinylation impairs collagen cross‐linking in various organs, including the heart, of Cbs −/− mice, thus providing an explanation for connective tissue deficiencies prevalent in HHcy humans . In small, case–control studies, elevated plasma Hcy‐thiolactone and N ‐Hcy‐protein are associated with vascular damage in diabetes and increased CAD risk , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen is a major extracellular matrix component of bone providing structural support coming from specific cross‐links involving lysine residues within and between collagen chains (Boskey, ). N‐homocysteinylation of these lysines was hypothesized to impair cross‐linking (Jackson, ; Lubec, Fang‐Kircher, Lubec, Blom, & Boers, ), but only recently proven in I278T mice (Perla‐Kajan et al., ), thus at least partially explaining skeletal and connective tissue defects in HCU. The study comparing Tg‐WT and I278T mice showed that, while the amount of bound Hcy to plasma proteins is similar, the amount of total free Hcy (i.e., sum of free reduced Hcy and Hcy from Hcy–Hcy and Hcy–Cys disulfides) was significantly higher in I278T mice suggesting that plasma proteins have a maximum binding capacity for Hcy (Gupta et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In this reaction, homocysteine thiolactone, an active cyclic thioester in which the carboxyl group is condensed with the sulfhydryl group, acylates the free amino groups of protein lysine residues [57]. The integration of homocysteine molecules with any given protein may significantly affect its functional domain, and therefore the entire protein function [58]. …”
Section: Mechanistic Studiesmentioning
confidence: 99%